Differential rates of replacement of human dermal dendritic cells and macrophages during hematopoietic stem cell transplantation - Haniffa, Muzlifah (The Rockefeller University Press, 2009)
Animal models of hematopoietic stem cell transplantation have been used to analyze the turnover of bone marrow–derived cells and to demonstrate the critical role of recipient antigen-presenting cells (APC) in graft versus host disease (GVHD). In humans, the phenotype and lineage relationships of myeloid-derived tissue APC remain incompletely understood. It has also been proposed that the risk of acute GVHD, which extends over many months, is related to the protracted survival of certain recipient APC. Human dermis contains three principal subsets of CD45(+)HLA-DR(+) cells: CD1a(+)CD14(−) DC, CD1a(−)CD14(+) DC, and CD1a(−)CD14(+)FXIIIa(+) macrophages. In vitro, each subset has characteristic properties. After transplantation, both CD1a(+) and CD14(+) DC are rapidly depleted and replaced by donor cells, but recipient macrophages can be found in GVHD lesions and may persist for many months. Macrophages isolated from normal dermis secrete proinflammatory cytokines. Although they stimulate little proliferation of naive or memory CD4(+) T cells, macrophages induce cytokine expression in memory CD4(+) T cells and activation and proliferation of CD8(+) T cells. These observations suggest that dermal macrophages and DC are from distinct lineages and that persistent recipient macrophages, although unlikely to initiate alloreactivity, may contribute to GVHD by sustaining the responses of previously activated T cells.